ETIKA KOMUNIKASI PESERTA DIDIK DIGITAL NATIVES MELALUI MEDIA KOMUNIKASI ONLINE (WHATSAPP) KEPADA PENDIDIK: PERSPEKTIF DOSEN - Nurul Fauziyyah (Nurul Jadid University, 2019)
This study aims to investigate the relationship between the ages of educators in several generations such as baby boomer, x generation, y generation, z generation, and alpha generation, classified into baby boomers, digital immigrants, and digital natives, with the communication ethics of students who incidentally as digital natives through online communication media (whatsapp). This study is a survey study conducted by distributing online research questionnaires through Google form to educators, especially lecturers from various regions and universities in Indonesia. The total of 219 educators participated in this study. Based on the results of a simple correlation test (r) using the Pearson method (Product Moment Pearson), it was found that there was a weak relationship between the age of educators and the communication ethics of students via whatsapp and the direction of the relationship was negative because the value of r was negative. These results indicate that there are other things that have relationship with students' communication ethics with educators.